Access and attitudinal barriers to engagement in integrated primary care mental health treatment for rural populations. Issue 4 (24th August 2021) - Newman, Mark W.; Hawrilenko, Matt; Jakupcak, Matthew; Chen, Shiyu; Fortney, John C.
Abstract: Purpose: Compared to urban areas, rural populations are less likely to engage in mental health care. Using data from the Study to Promote Innovation in Rural Integrated Telepsychiatry, we examined the effect of rurality on engagement in mental health treatment as well as the role of potential mediators. Methods: Data were obtained from medical records and surveys. We defined rurality using the rural‐urban commuting area codes. Baseline mediators included the Endorsed and Anticipated Stigma Inventory and the Assessment of Perceived Access to Care. Engagement outcomes included number of psychotherapy visits and self‐reported medication use. We used path analysis to examine the relationship between rurality and engagement and the influence of mediating variables. Findings: Rural participants were less likely to initiate psychotherapy (OR = 0.49; adjusted P = .036), although rurality was not associated with number of psychotherapy sessions or medication use. Rurality was associated with a small elevation in negative beliefs about mental health, but this potential mediator was not associated with engagement. Rurality was negatively associated with lower perceived need for treatment (OR = 0.67, adjusted P = .040), which was in turn positively associated with initiating psychotherapy (OR = 1.99, adjusted P = .001). Conclusions: Neither rurality itself nor the potential mediators had a large effect on engagement. Federally Qualified Health Centers offering colocated and/or integrated mental health care appear to be mostly mitigating rural‐urban disparities in mental health engagement. Improving rates of psychotherapy initiation for rural patients should remain a policy goal.